Using Drama in EFL Classroom - Angelianawati, Luh (JET (Journal of English Teaching), 2019)
Due to the many potential benefits and drama can offer in language learning, there has been a growing interest to use drama in ESL/EFL classrooms. However, the practice still causes many difficulties to both teachers and students due to several factors. This article reviews current theories and research findings on the use of drama in ESL/EFL teaching and learning to provide a better understanding of the use of drama to facilitate learning in EFL classrooms. It begins with current theories behind drama use in English learning. This section tries to clarify what drama is in the context of ESL/EFL, what benefits it offers, and what challenges teachers potentially meet. After that, the discussion focuses on a practical guideline for using drama in the classroom. It proceeds with a brief description of some useful drama techniques. The article ends by offering some concluding remarks.